The Stepsure Letters: Puritanism and the Novel Of the Land - Mathews, Robin (Studies in Canadian Literature, 1982)
Thomas McCulloch’s The Stepsure Letters belongs to the genre known as "the novel of the land." It has more in common with le roman de la terre in Quebec than with typical Calvinist fiction. In McCulloch’s novel, characters and identities are shaped by the land. This is in marked opposition to the fiction of the United States and England. T.C. Haliburton’s The Clockmaker is philosophically influenced by The Stepsure Letters. This philosophy is essentially that of the legitimacy, morality, and viability of the land life as opposed to the basic degeneracy of the commercial life.